2014
DOI: 10.1111/joa.12214
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of femorotibial joint geometry in the trochlear dysplastic femur

Abstract: The medial and lateral tibia plateau geometry has been linked with the severity of trochlear dysplasia. The aim of the present study was to evaluate the tibial slope and the femoral posterior condylar offset in a cohort of consecutive subjects with a trochlear dysplastic femur to investigate whether the condylar offset correlates with, and thus potentially compensates for, tibial slope asymmetry. Magnetic resonance imaging was used to assess the severity of trochlear dysplasia as well as the tibial slope and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Frosch et al found a positive correlation between the medial femoral condylar offset and the medial tibial slope. A greater medial tibial slope indicates a larger offset of the medial femoral condyle, in patients with TD [10]. These data support the results of the present study, which shows a correlation between the AP length of the medial condyle and TD.…”
Section: Discussionsupporting
confidence: 92%
“…Frosch et al found a positive correlation between the medial femoral condylar offset and the medial tibial slope. A greater medial tibial slope indicates a larger offset of the medial femoral condyle, in patients with TD [10]. These data support the results of the present study, which shows a correlation between the AP length of the medial condyle and TD.…”
Section: Discussionsupporting
confidence: 92%
“…The morphology of the distal femur is complex [1][2][3][4]. Various studies showed that medial and lateral femoral condyle morphology differ in ACO, PCO and length [23][24][25][26]. In this context, the current literature raises the question of whether the existing standard implants for arthroplasty of the knee joint adequately consider the physiological morphology of femoral condyles [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…A case–control study of 186 knees (98 TD vs 88 controls) demonstrated a positive correlation between the medial femoral condylar offset and the medial tibial slope in trochlear dysplastic knees. A greater degree of the medial tibial slope indicated a larger offset of the medial femoral condyle [13]. A study that analysed the ratio of the tibial tuberosity–trochlear groove distance (TT‐TG) to the tibial maximal mediolateral axis in trochlear dysplastic knees reported no difference in ML width of the tibial plateau between trochlear dysplastic and normal knees [6].…”
Section: Discussionmentioning
confidence: 99%